2016
DOI: 10.1177/0974686216635787
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ownership Structure and Board Composition on Corporate Performance in Indian Companies

Abstract: This study takes into account the National Stock Exchange (NSE)-listed Indian companies, which constitute the CNX Nifty Index, for the period from 1 April 2009 to 31 March 2013. Tobin's Q, market value added, cash earnings per share and return on capital employed have been used as the corporate performance variables in the study; the first two being market-based and the last two being accounting-based measures. Board size (BS), board composition, ownership structure, multiplicity of directorship, chief executi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
48
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(66 citation statements)
references
References 27 publications
12
48
2
1
Order By: Relevance
“…Recent empirical evidences like Bae et al (2018) in the context of three South Asian countries under a cross-country analysis and Haque and Ntim (2018) in the context of UK listed firms also endorse the positive association between the board size and environmental performance of firms. Besides, the findings of our study are also endorsing the view of Klein (2002) and Manna, Sahu, and Gupta (2016) that a board with large number of members is supposed to allow specialisation in direction, which in turn can lead to more effectiveness in many dimensions of a company’s performance including its market value.…”
Section: Discussionsupporting
confidence: 78%
“…Recent empirical evidences like Bae et al (2018) in the context of three South Asian countries under a cross-country analysis and Haque and Ntim (2018) in the context of UK listed firms also endorse the positive association between the board size and environmental performance of firms. Besides, the findings of our study are also endorsing the view of Klein (2002) and Manna, Sahu, and Gupta (2016) that a board with large number of members is supposed to allow specialisation in direction, which in turn can lead to more effectiveness in many dimensions of a company’s performance including its market value.…”
Section: Discussionsupporting
confidence: 78%
“…For instance, when exploring the effect of ownership structure on the firm’s performance, Kumar (2004) found that the foreign shareholding pattern did not influence significantly the firm’s performance in India. This result contrasted with other studies which found that foreign ownership lead to higher performance of firms in India (Manna, Sahu, & Gupta, 2016).…”
Section: Literature Reviewcontrasting
confidence: 99%
“…For instance, when exploring the effect of ownership structure on the firm's performance, Kumar (2004) found that the foreign shareholding pattern did not influence significantly the firm's performance in India. This result contrasted with other studies which found that foreign ownership lead to higher performance of firms in India (Manna, Sahu, & Gupta, 2016). Brown and Caylor (2009) studied the relationship between corporate governance variables and firm operating performance in USA, using a composite measure of corporate governance (governance index), and found that bettergoverned firms are relatively more profitable, more valuable and pay out more cash to their shareholders.…”
Section: Literature Reviewcontrasting
confidence: 76%
“…Manna et al (2016),Mishra and Kapil (2017) are found to be consistent with our ndings. Regarding institutional type of ownership and rm valuation our ndings go in line with the studies ofDouma et al (2006),Ghosh (2007) in context of Indian market and McConnell and Servaes (1990) on U.S. market context, Sahuta and Gharbib (2010) in context of French rms, Ting (2013) on Taiwan market etc.…”
supporting
confidence: 92%